Molecular Characterizations of a High Pathogenic Avian Influenza H5N8 in Iraq - Ahmed Neama Mahmood1 , Aida Bara Allawe2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
High pathogenicity avian influenza subtype H5N8 viruses were detected in different areas in Iraq at thelast 2017 and early 2018 and 2019 and the disease was detected clinically. This disease is responsible forhigh economic losses for poultry industry and threat human health, so that, this study was conducted formolecular detection, characterization and phylogenic analysis of avian influenza in Iraq. AI subtype H5N8 isan infectious disease primarily in birds and responsible for severe respiratory illness which associated witha high percentage of morbidity and mortality in wild and domestic birds. During this study one hundred fiftydifferent samples including (trachea, larynx and lung) were collected from different areas of broiler chickenfrom Baghdad and its surrounding regions during winter 2019. Avian influenza virus subtype H5N8 wasdetected by using real time RT-PCR technique, and specific kits (KyltR Germany) for AIV subtypes H5 andN8 were used respectively. The results revealed that (15) samples out of (150) collected samples were gavepositive results for avian influenza H5 these positive samples were prepared for a second step of detectionby RT-PCR test specific for N8 subtype the results revealed that only (12) out of (15) tested samples werepositive for H5N8 (8%).Genetic sequencing of isolates and phylogenic analysis of three selected isolates of(H5N8) bellowing to different areas indicate that all strains bellowing to H5 class (2.3.4.4) high pathogenicavian influenza revealed that they are closely related to Egyptian strain (A/ duck/ Egypt/ F446/2017.H5N8-MH893737.1) (with 97.6% identity). Analysis of the mono-basic amino acid (PQIEPR / GLF) atthe hemagglutinin cleavage site revealed there is no deletion of the stalk region with the neuraminidaseindicated that the isolates is a typical HPAI strain (A / duck / Egypt / F446/2017). The similarity of thenucleotide sequence analysis of hemagglutinin gene revealed that there was a high homology (97.6%) to thatof A/duck/Egypt/F446/2017 H5N8 .